Nasal cavity paranglioma - Paule, Pilar Navarro (1969)
Paraganglioma tumour is a neuroendocrine neoplasm that is presented in extra-adrenal si te in the 5-10% of the cases. We present the case of a fifty three year-old woman with a para ganglioma located in the nasal cavity, being this localization extremely rare. We describe the diagnostic methods, treatment and the prognosis of the patient.